Effects of supplementary feed on food preference of rohu Labeo rohita in mono and polyculture systems - Rahman, Mohammad Mustafizur; Verdegem, Marc C.J. (2005)
Rohu (Labeo rohita) has been used as an important aquaculture species in Southeast Asia specially in Bangladesh and India. However, because of its higher consumer preference, higher market value, as well as exploiting food from whole water column, farmers like more to stock rohu in their pond either in monoculture or in polyculture with another bottom feeder fish like common carp (Cyprinus carpio). Rohu is very dependant on natural food but farmers get higher production of rohu when they use supplementary feed in their pond. Due to lack of real recommendations on how supplementary feed influences the food habit and growth of rohu, an experiment was carried out in 18 earthen ponds to know the effects of supplementary feed on natural food availability in the pond, their ingestion and growth performance of rohu. All ponds were fertilized each fortnightly with fertilizer: 1,250.0 kg ha-1 decomposed cow manure, 31.25 kg ha-1 urea and 156.63 kg ha-1 triple super phosphate. Half of the ponds received supplementary feed, the others ponds received no feed. All ponds were stocked with 1.5 rohu m-2. Three common carp densities: 0, 0.5 and 1.0 common carp m-2 were used with and without supplementary feed. The combinations gave following six treatments: rohu alone with and without feed; rohu plus 0.5 common carp m-2 with and without feed; and rohu plus 1.0 common carp m-2 with and without feed. It was found, supplementary feed had no significant effect on phytoplankton availability whereas there was strong significant effect on zooplankton availability in the ponds water. Zooplankton was significantly higher in treatments with feed than no feed. Treatments with feed showed better growth performance of rohu than the treatments with no feed. Monthly volumetric gut content analysis showed, rohu generally ingest phyto- plankton better than zooplankton but in presence supplementary feed rohu ingest more zooplankton than phytoplankton. Rohu shifts food habit from phyto- plankton to zooplankton when zooplankton is easily available in the ponds in presence of supplementary feed. This shifting behaviour proves, rohu prefer zooplankton better than phytoplankton. This behaviour also may be affected by others various physico-chemical factors.